Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Team $A$ is playing team B in a series of three games. Team $A$'s probability of winning any particular game is nonzero, independent of other games, and is $1.6$ times as large as its probability of winning the series. What is the probability of team $A$ winning the series?

My approach :

Let the probability of winning any game be $x$, then $$x = 1.6 \left( x^3 + 3x(1 -x) \right)$$ because the series can be won as WWW, WLW, LWW, WWL.

Please help.

share|cite|improve this question
up vote 4 down vote accepted

Yes your approach is indeed correct. However, the equation you have obtained is incorrect. You will obtain $$x = 1.6(x^3 + 3\color{red}{x^2}(1-x)).$$ Since you are given that the probability of $A$ winning a game is non-zero, we can cancel off the $x$ to get $$5 = 8 (x^2 + 3x -3x^2) = -16x^2 + 24x \implies 16x^2 - 24x + 5 = 0$$ Now solve the above quadratic equation, with the constraint the $0 <x < 1$.

$$16x^2 - 24x + 5 = 0 \implies x = \dfrac{24 \pm \sqrt{24^2 - 4 \times 16 \times 5}}{2 \times 16} = \dfrac34 \pm \dfrac12 = \dfrac14, \dfrac54.$$ Since $x$ denotes, a non-zero probability, we get that the desired probability is $x = \dfrac14$.

share|cite|improve this answer
Yes sir Marvis, sorry, it was a a typo. I'm getting answer as 5/32. Thanks for helping me. You're awesome. – Bazinga Jun 30 '12 at 15:58

You equation isn’t quite right: the probability that $A$ wins a $WWL$ series is $x^2(1-x)$, not $x(1-x)$. Thus, the equation should be $x=1.6\big(x^3+3x^2(1-x)\big)$. Multiply out the righthand side to get $1.6(x^3+3x^2-3x^3)=1.6(3x^2-2x^3)=4.8x^2-3.2x^3$, and combine everything on one side of the equation: $3.2x^3-4.8x^2+x=0$. You can get rid of the decimals by multiplying through by $5$ to get $16x^3-24x^2+5x=0$. Now factor out the obvious common factor: $x(16x^2-24x+5)=0$. One solution is $x=0$, but you’ve been told that this isn’t the solution, so it must be the case that $16x^2-24x+5=0$. That’s just a quadratic, so it’s easy to solve.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.